La rivisitazione dell’idea di “spirito” nell’antropologia personalistica di Romano Guardini - Miranda, Davide (Alpha omega, 2019)
The main objective of this project lies in the presentation of the most relevant features of Romano Guardini’s concept of ‘person’, as characterised by the presence of the spiritual dimension, which determines the person and his freedom as irreducible to other entities, and which thus determines the inviolability of his human dignity. The aim of this reflection will be to put forward a model of anthropology, which, in contradistinction to modern orientations of an idealistic kind, the ‘spirit’ appears as disconnected from its being levelled down to the ‘io’, understood in an immanentist sense, as pure subject, who orientates his activism as dominion over the world, and is bound to the idea of the interior centre of the person, as his point of balance, and as the source of the different and opposing vital tendencies, as the place in which man must enter into the full, free possession of his existence, reconnecting himself with his divine origin and re-appropriating his essence, as a ‘spirit’ truly involved in the complexity and multi-dimensional nature of the human person.